Highly Pathogenic Avian Influenza H5N1, Thailand, 2004 - Thanawat Tiensin; Prasit Chaitaweesub; Thaweesak Songserm; Arunee Chaisingh; Wirongrong Hoonsuwan; Chantanee Buranathai; Tippawon Parakamawongsa; Sith Premashthira; Alongkorn Amonsin; Marius Gilbert; Mirjam Nielen; Arjan Stegeman (Emerging Infectious Diseases, 2005)
In January 2004, highly pathogenic avian influenza (HPAI) virus of the H5N1 subtype was first confirmed in poultry and humans in Thailand. Control measures, e.g., culling poultry flocks, restricting poultry movement, and improving hygiene, were implemented. Poultry populations in 1,417 villages in 60 of 76 provinces were affected in 2004. A total of 83% of infected flocks confirmed by laboratories were backyard chickens (56%) or ducks (27%). Outbreaks were concentrated in the Central, the southern part of the Northern, and Eastern Regions of Thailand, which are wetlands, water reservoirs, and dense poultry areas. More than 62 million birds were either killed by HPAI viruses or culled. H5N1 virus from poultry caused 17 human cases and 12 deaths in Thailand; a number of domestic cats, captive tigers, and leopards also died of the H5N1 virus. In 2005, the epidemic is ongoing in Thailand.